2007
DOI: 10.1007/s10704-008-9213-7
|View full text |Cite
|
Sign up to set email alerts
|

Fracture assessment of U-notches under mixed mode loading: two procedures based on the ‘equivalent local mode I’ concept

Abstract: Two fracture criteria are proposed and applied to blunt-notched components made of brittle materials loaded under mixed mode; the former is based on the averaged strain energy density over a given control volume, the latter on the cohesive crack zone model. In both instances use of the equivalent local mode I hypothesis is made. Only two material properties are needed: the ultimate tensile strength and the fracture toughness. Numerical predictions of rupture loads from the two criteria are compared with experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
103
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 148 publications
(107 citation statements)
references
References 67 publications
(73 reference statements)
4
103
0
Order By: Relevance
“…In previous works by the authors [28,[37][38][39] tensile tests with PMMA specimens at low temperatures had shown an almost linear elastic mechanical behaviour up to failure (see Fig. 8a).…”
Section: Resultsmentioning
confidence: 72%
See 4 more Smart Citations
“…In previous works by the authors [28,[37][38][39] tensile tests with PMMA specimens at low temperatures had shown an almost linear elastic mechanical behaviour up to failure (see Fig. 8a).…”
Section: Resultsmentioning
confidence: 72%
“…The problem becomes more involved if the loading symmetry is lost, i.e. when the notched structural component is subjected to mixed mode loading as widely discussed in previous works by other researchers [31][32][33][34][35][36] and also by the present authors [37][38][39][40][41][42].…”
Section: Introductionmentioning
confidence: 76%
See 3 more Smart Citations